Analysis of concrete crack growth based on micro‐plane model. (24th October 2017) - Peyman, Farzad; Sadrnejad, Seyed A.
Abstract : The crack geometry effect is encountered in compliance matrix as a tensor containing 17 on‐plane stress/strain component interrelation. The components of compliance matrix vary due to the effects of the directional fabric behavior of the material created by inherent/induced anisotropy that can be differed in any of the multi‐direction through material. Mathematically, any alterations in multi‐directional material behavior are numerically integrated and affected in material compliance matrix. The main objective of this paper is to develop a numerical approach to determine the crack initiation and its growth for brittle materials such as concrete. Upon the numerical integration technique, any multi‐directional behavior aspect is affected by components of compliance matrix to reflect historically in the next step material behavior. Accordingly, the proposed model results are investigated to satisfy both equilibrium and compatibility equations. In this paper, previous selected 13 sampling points in numerical integration are updated to 17 planes to overcome the compatibility problem. To show the capability of the model, a few fractured concrete test results under different loading stress/strain paths were examined. The significant advantage of the proposed multi‐laminate model is to present a complete pre‐failure history of stress/strain progress on different predefined sampling planes which leads to the illustration of the final damaged or failure mechanism.